The effect of religiosity on life satisfaction: A meta-analysis - Sholihin, Muhammad (HTS teologiese studies, 2022)
This article intends to synthesise the results of various studies related to the influence of religiosity on life satisfaction, with the aim of mapping how religiosity variables influence people’s life satisfaction in multiple countries. Additionally, this study seeks to identify the development of research issues regarding religiosity and life satisfaction. For this reason, a meta-analysis approach was applied to synthesise 21 articles quantitatively, and the systematic literature review (SLR) approach was used to narrate the development of issues concerning religiosity and life satisfaction in 40 articles. In general, this study succeeds in demonstrating that the influence of the religiosity variable on life satisfaction in various study samples is linear and has a positive effect.Contribution: The dimensions of religiosity and life satisfaction are still very limited to the characteristics of disciplines attached to researchers. This resulted in the dimension being repeatedly used (redundancy) in various studies, resulting in the second dimension of the issue (i.e., religiosity and life satisfaction) being less developed. Therefore, it contributes to the issues as a foundation of new directions, i.e., emic perspectives, in understanding the relationship between religiosity and life satisfaction.